ANALISIS IMPLEMENTASI ARTIFICIAL INTELLIGENCE SEBAGAI ALAT BANTU PEMBELAJARAN MATEMATIKA - Dian Elita Apriani Dian; Dwita Lestari Saragi; Romaulika Situmorang; Samuel Yordan Ambarita; Sri Vioni Novena Simanihuruk; Glory Indira Diana Purba (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The integration of digital technology, particularly artificial intelligence, is crucial in addressing the challenges of mathematics learning in higher education, which often triggers cognitive anxiety and low student interest due to overly theoretical conceptualization. This study aims to analyze the implementation of intelligent systems as a tool to bridge psychological barriers and increase learning motivation through a personalized approach. The research method employed a descriptive literature review of sixteen reputable scientific articles from 2020 to 2025. The systematic steps included data identification, raw information reduction, narrative presentation, and drawing conclusions through continuous verification. The research findings indicate that instant feedback features and algorithm-based dynamic visualizations can strengthen the depth of understanding of mathematical concepts independently. The adaptive learning system successfully creates a flexible learning experience that accommodates individual pace, thus further enhancing the transformation of students into active subjects. However, structural barriers such as limited technological infrastructure and low digital literacy among educators remain major obstacles to the distribution of quality intelligent education. The main conclusion confirms that although artificial intelligence has transformative potential in boosting academic achievement and critical thinking skills, its success is highly dependent on the readiness of human resources and the support of adequate institutional facilities to create an inclusive, modern, and progressive mathematics learning ecosystem in the future for the advancement of a more effective global educational civilization.